Penanaman Modal Asing, Penanaman Modal Dalam Negeri Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Indonesia Dalam Perspektif Ekonomi Islam Tahun 2019-2023 - Anggi Fadila; Dinda Fali Rifan; Gustika Nurmalia (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The issue raised is the imbalance between FDI, DDI, and government spending with the fluctuating economic growth rate from 2019 to 2023. This study aims to analyze the effect of Foreign Direct Investment (FDI), Domestic Investment (DDI), and Government Expenditure on Economic Growth in Indonesia from 2019 to 2023 from an Islamic economic perspective. The method used is a quantitative approach with panel data regression analysis using Eviews 10 software on data from 34 provinces in Indonesia. The results show that the three variables, namely FDI, DDI, and government spending, have a positive and significant effect on economic growth in Indonesia, both partially and simultaneously. From an Islamic economic perspective, economic growth is viewed not only in terms of increased output, but also in terms of justice, welfare, and the benefit of society. Therefore, investment and government expenditure policies should be managed in accordance with the principles of justice and sustainability as taught in Islamic values.